2002
DOI: 10.1007/s00280-001-0412-4
|View full text |Cite
|
Sign up to set email alerts
|

Cellular levels of aldehyde dehydrogenases (ALDH1A1 and ALDH3A1) as predictors of therapeutic responses to cyclophosphamide-based chemotherapy of breast cancer: a retrospective study

Abstract: Given (1) the wide range of ALDH1A1 levels observed in malignant breast tissues, (2) that ALDH1A1 levels in primary breast tumor tissue, as well as those in normal breast tissue, directly reflect ALDH1A1 levels in metastatic breast tumor cells derived therefrom, and (3) the findings reported here, measurement of ALDH1A1 levels in primary breast malignancies and/or normal breast tissue prior to the initiation of chemotherapy is likely to be of value in predicting the therapeutic potential, or lack of potential,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
151
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(160 citation statements)
references
References 23 publications
0
151
0
4
Order By: Relevance
“…Apoptotic resistance is crucial for distant metastasis as breast cancer cells must survive for extended periods of time in the circulatory system to reach distant organs, such as the lung, a condition in which they are exposed to high risk of anoikis (56). A particularly interesting gene in the SND1-regulated lung metastasis enrichment core is ALDH3A1, which has been shown to promote resistance to various chemotherapeutic agents and other cell death-inducing toxins (57)(58)(59). Importantly, ALDH3A1 was also shown previously to promote MTDH-mediated resistance to chemotherapy-induced apoptosis (6).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic resistance is crucial for distant metastasis as breast cancer cells must survive for extended periods of time in the circulatory system to reach distant organs, such as the lung, a condition in which they are exposed to high risk of anoikis (56). A particularly interesting gene in the SND1-regulated lung metastasis enrichment core is ALDH3A1, which has been shown to promote resistance to various chemotherapeutic agents and other cell death-inducing toxins (57)(58)(59). Importantly, ALDH3A1 was also shown previously to promote MTDH-mediated resistance to chemotherapy-induced apoptosis (6).…”
Section: Discussionmentioning
confidence: 99%
“…Seven of the eight validated genes overexpressed in current smokers-CYP1B1, four AKRs, ALDH3A1, and NQO1 (Table 2)-are involved in drug and/or carcinogen metabolism (9,10,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Polycyclic aromatic hydrocarbons in tobacco smoke are known to bind to and activate the aryl hydrocarbon receptor and thus induce CYP1B1 (10).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Storms et al demonstrated that primitive hemtopoietic progenitors could be purified with ALDH activity suggesting, that ALDH1 might be a reliable marker for the isolation of stem cells (17). Increased ALDH1 activity has also been found in stem cell populations in acute myeloid leukemia and breast cancers, as well as their normal counterparts; mammary and hematopoietic stem cells, and has been found to be correlated with drug resistance and poor prognosis of patients (18)(19)(20). Thus, ALDH1 has been proposed as a common marker for both normal and malignant stem cells.…”
Section: Introductionmentioning
confidence: 95%